2006
DOI: 10.1093/brain/awl204
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the amusic brain: a two-site study

Abstract: Congenital amusia (or tone deafness) is a lifelong disability that prevents otherwise normal-functioning individuals from developing basic musical skills. Behavioural evidence indicates that congenital amusia is due to a severe deficit in pitch processing, but very little is known about the neural correlates of this condition. The objective of the present study was to investigate the structural neural correlates of congenital amusia. To this aim, voxel-based morphometry was used to detect brain anatomical diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
152
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 58 publications
19
152
1
3
Order By: Relevance
“…Structural neuroimaging data reveal subtle differences in the brains of individuals with congenital amusia, in inferior frontal cortex and superior temporal areas, variously in the left hemisphere (Hyde et al, 2007;Hyde, Zatorre, Griffiths, Lerch, & Peretz, 2006) or the right (Mandell, Schulze, & Schlaug, 2007). An understanding of how these biological differences relate to the behavioural deficits previously mentioned is currently far from clear, but the finding of morphological differences outside the temporal cortex are congruent with findings from functional imaging studies showing activation of frontal and temporal areas when pitch information must be integrated or compared over time (Gaab, Gaser, Zaehle, Jancke, & Schlaug, 2003;Koelsch et al, 2009;Levitin & Menon, 2003;Zatorre, Evans, & Meyer, 1994).…”
Section: Biological Basismentioning
confidence: 99%
“…Structural neuroimaging data reveal subtle differences in the brains of individuals with congenital amusia, in inferior frontal cortex and superior temporal areas, variously in the left hemisphere (Hyde et al, 2007;Hyde, Zatorre, Griffiths, Lerch, & Peretz, 2006) or the right (Mandell, Schulze, & Schlaug, 2007). An understanding of how these biological differences relate to the behavioural deficits previously mentioned is currently far from clear, but the finding of morphological differences outside the temporal cortex are congruent with findings from functional imaging studies showing activation of frontal and temporal areas when pitch information must be integrated or compared over time (Gaab, Gaser, Zaehle, Jancke, & Schlaug, 2003;Koelsch et al, 2009;Levitin & Menon, 2003;Zatorre, Evans, & Meyer, 1994).…”
Section: Biological Basismentioning
confidence: 99%
“…More specifically, functional imaging studies indicate that areas of the auditory cortex within the right superior temporal gyrus are involved in r Oscillations and Synchronization in Musical Syntax r r 1221 r the processing of pitch and timbre [Zatorre, 1988;Zatorre and Samson, 1991], and that working memory for pitch entails interaction between temporal and frontal cortices [Zatorre et al, 1994]. Hyde et al [2006] found, in the brains of individuals with amusia (tone deafness), white matter changes in the right IFG area (BA 47) as correlates of a musical pitch processing, which was interpreted as an anomalous connectivity between frontal and auditory cortical areas. A PET study [Blood et al, 1999] reported positive correlations of activity in orbitofrontal and bilateral frontopolar cortex with increasing dissonance, and the predominance of inferior frontal areas has been further demonstrated in an fMRI study investigating musical syntax processing where activation of this region increased for strong musical expectancy violations [Tillmann et al, 2003], but also for more subtle harmonic irregularities [Tillmann et al, 2006].…”
Section: Decrease In Long-range Alpha Band Phase Synchronizationmentioning
confidence: 99%
“…Used to describe individuals born with a lifelong musical impairment, empirical work into the condition has confirmed that amusia is a genuine perceptual agnosia, characterized by deficits in melody recognition and discrimination (Stewart, von Kriegstein, Warren, & Griffiths, 2006). Neuroimaging studies have suggested that the musical difficulties observed in individuals with amusia are related to subtle differences in brain structure and connectivity (Hyde, Zatorre, Griffiths, Lerch, & Peretz, 2006;Loui, Alsop, & Schlaug, 2009;Mandell, Schulze, & Schlaug, 2007) and the condition appears to be hereditary (Drayna, Manichaikul, de Lange, Snieder, & Spector, 2001;Peretz, Cummings, & Dubé, 2007).…”
mentioning
confidence: 99%